PERAN BADAN PEMBERDAYAAN MASYARAKAT PEMERINTAHAN DESA (BPMPD) MELALUI PROGRAM PENINGKATAN PEMBERDAYAAN MASYARAKAT PERDESAAN DI KECAMATAN KUNDUR BARAT KABUPATEN KARIMUN (STUDI PADA DESA SAWANG LAUT DAN DESA GEMURUH) TAHUN 2013 - Kurniadi, Edy; ", Muchid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aimed to determine the issue of how Role of Community Empowerment and Village Government of National Unity (BPMPD and Unity) Karimun through Enhancement Program for Community Empowerment in Rural Areas in the District of West Kundur Karimun (Studies in Sawang Sea village and Gemuruh village). The method used in this study using qualitative research methods, data collection techniques through direct interviews to the informant.The results of the study The Role of Rural Community Empowerment Board and the Government of National Unity ( BPMPD and Unity ) Karimun through Enhancement Program for Community Empowerment in Rural Areas in the District of West Kundur Karimun (Studies in Sawang Sea village and Rumbling village), which is to develop and empower local potential sources existing power that each delivered development efforts through empowerment, basically aimed at achieving changes in people's behavior in order to realize improved quality of life that includes many aspects, economic, social, cultural, ideological, political, and defense and security. This occurs due to the inhibiting factors in the development and management of potential areas, namely : Community empowerment has been done is not directional and are not caused by factors focus funding for development is still minimal. Minimal Human Resources, Facilities and Infrastructure inadequate, customs and culture that are so thick and social influence local politics .Keywords: Roles, Policies, Empowerment and Development